Digital Transformation in Public Administration Through Artificial Intelligence to Enhance Bureaucratic Performance - Karlina Napu; Risna Sanaba (Journal of Creative Power and Ambition (JCPA), 2026)
This study examines digital transformation in public administration through artificial intelligence (AI) as an effort to enhance bureaucratic performance in the contemporary governance environment. The research employs a qualitative literature review approach by analyzing secondary data derived from scientific journal articles, books, policy reports, and official publications published predominantly from 2020 onward. The study explores how AI contributes to bureaucratic performance by improving administrative efficiency, accelerating public service delivery, supporting data-driven decision-making, and transforming the role of bureaucracy toward more adaptive and citizen-oriented governance. The findings indicate that AI has significant potential to automate repetitive administrative tasks, optimize workflows, enhance service accessibility, and strengthen the analytical capacity of public institutions in managing complex public demands. At the same time, the study finds that the successful implementation of AI in public administration depends on institutional readiness, digital infrastructure, human resource competence, interoperable information systems, and effective governance mechanisms. The research also highlights that AI-based bureaucratic transformation raises important concerns related to accountability, transparency, algorithmic bias, public trust, and ethical oversight, which must be addressed to ensure that technological innovation aligns with democratic values and public sector responsibility. Therefore, digital transformation through AI should be understood not only as a technological modernization strategy but also as a comprehensive administrative reform that can improve bureaucratic performance when supported by institutional capacity, regulatory safeguards, and a strong commitment to public value.